Combined BAC and MIEX pre-treatment of secondary wastewater effluent to reduce fouling of nanofiltration membranes - Aryal, Ashok; Sathasivan, Arumugam; Heitz, Anna; Gang, Z.; Nikraz, Hamid; Ginige, M. (IWA Publishing, 2015)
Biological activated carbon (BAC) and magnetic ion exchange resin (MIEX) were used to pre-treat secondary wastewater effluent (SWWE) and assessed for their capacity to reduce fouling of a nanofiltration membrane. BAC pre-treated water facilitated a lower but a steady flux while MIEX treated water resulted in a higher but a rapidly declining flux. Their combined use increased average flux from 58 to 89%. MIEX combined with BAC, in that order, was superior in reducing membrane fouling. Measurement of average Stokes radius (m) and apparent molecular weight distribution of dissolved organic matter (DOM), by nuclear magnetic resonance (NMR) and liquid chromatography organic carbon detection (LC-OCD), respectively, revealed that the microbial activity of BAC changed the nature of organic matter, probably by increasing the size of DOM molecules. BAC generally decreased the lower apparent molecular weight (LMW) fraction of dissolved organic carbon (DOC). Hence, the removal of LMW DOC and an increase of average Stokes radius (m) of DOM appeared to be important in facilitating a longer steady flux. Specifically, the combined MIEX/BAC pre-treatments appeared to target and reduce the foulants in SWWE that are largely responsible for the reduction of flux in nanofiltration membranes.